Sterol synergism in yeast. - Ramgopal, M (1983)
Sterol synergism as previously observed [Dahl, C.E., Dahl, J.S. & Bloch, K. (1980) Biochemistry 19, 1462-1467] and defined as a greater-than-additive growth response to pairs of sterols by Mycoplasma capricolum [Dahl, J.S., Dahl, C.E. & Bloch, K. (1981) J. Biol. Chem. 256, 87-91] is now demonstrated in the yeast mutant GL7, which is auxotrophic for sterol and unsaturated fatty acid. Mutant cells growing poorly when provided with cholesterol and oleic acid respond to ergosterol supplements (ergosterol-to-cholesterol ratio, 1:3) by a pronounced increase in growth rates and cell yields. Stigmasterol also elicits a significant synergistic effect, and 7-dehydrocholesterol, a smaller one. Evidence for a metabolic role of ergosterol in yeast membranes is presented. Cells raised on a 1:3 mixture of ergosterol to cholesterol up to midlogarithmic phase subsequently incorporate [1-14C]oleic acid at significantly faster rates into phospholipids than do cells grown on cholesterol alone.